Reports - Filipenko, Volodymyr; Shevchenko, Olena; Smolynskyy, Oleksandr; Klepach, Mykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Report of the societies and associations of orthopedic trauma of Ukraine.